Słownik a poezja : z zagadnień świadomości leksykalnostylistycznej polskiego Oświecenia - Maćkowiak, Krzysztof (1963- ) (Zielona Góra: Wydawnictwo Wyższej Szkoły Pedagogicznej)
The book presented here consists of three parts. The first one deals with the issue of exploiting the collective linguistic awareness (which is composed, generally, of the linguistic convictions common to a given social group) as a context in stylistic survey as well as the problems of reconstructing that awareness.
Keywords: język polski - stylistyka - 18 w.; język polski - słownictwo - 18 w.; poezja polska - 18 w.; stylistyka; literatura oświecenia; oświecenie - literatura; świadomość językowa; 18 w.